RELATIVE FREQUENCY OF HEPATITIS B VIRUS AND HEPATITIS C VIRUS INFECTIONS IN PATIENTS OF LIVER CIRRHOSIS IN CHILDREN - Syed Nizam Hussain Shah; Muhammad Asim Ikram (Journal of University Medical & Dental College, 1970)
ABSTRACT Objectives: To determine the relative frequency of Hepatitis B virus and Hepatitis C virus infections in liver cirrhosis in children between 5 to 15 years. Study design: Descriptive case series. Setting and Duration: The Gastroenterology Department at The Children’s Hospital, Lahore from August 2008 to July 2009 Subjects and methods: A total of 100 children diagnosed as liver cirrhosis on the basis of clinical features and ultrasonography findings were analyzed for findings and viral serology. Results: Mean age was 10.14 years and male to female ratio was 2:1. Out of 100 patients, 14 were infected with HBV, 8 with HCV. No case was found positive for both viruses. In HBsAg positive group, 12 were male and 2 were female (p=0.045). Conclusions: Both viruses account for 22% cases of liver cirrhosis in children. Liver cirrhosis due to HBV is more common than HCV in this region.